THE STUDENT’SLEARNING RESULT USING COOPERATIVE LEARNING MODEL TYPE PAIR CHECKS ON MATERIAL REQUIREMENTS, EQUIPMENT, HEALTH AND SAFETY IN CLASS X TECHNICOF CONSTRUCTION STONE AND CONCRETE SMK NEGERI 1 PALANGKA RAYA 2015/2016 - Firdaus Saputra; Samuel Layang (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2016)
Based on observations and interviews with productive subjects teachers in grade X of Stone and Concrete SMK Negeri - 1 Palangkaraya, students understand less and very rare to ask with the result that the learning is teacher focused. Be based the final evaluation, 70% of students score less than 70 which has not reached the value of Minimum Exhaustiveness Criteria (KKM) that implemented by the school with curriculum KTSP. This study aims to determine the learning results of students through Cooperative Learning Model Type Pair Checks on the subject matter requirements, health and safety equipment inthe students of class X TKBB SMKN-1 Palangka Raya academic year 2015/2016. This research is categorized as descriptive research with quantitative approach method by using Pair Checks type cooperative learning model on student learning results on the subject requirements, health and safety equipment in class X Technic of Stone and Concrete SMK Negeri 1 Palangka Raya, academic year 2015/2016 with 32 students for experimentalgroup and another 32 students from Department of Building Image Engineering for the control group. The research results showed that posttest of the experimental group (X2 = 3.0111 <X2table = 11,070) and the control group (X2 = 2,2299 <X2tabel = 11,070) were normal and homogeneous distributed (Fhitung = 1.60 <Ftabel = 1.82).The average results of posttest of the experimental group was 88 and the control group was 71,553. The analysis of the data used in this research is t-test at 5% significant level that means (thitung = 5.32> ttabel = 1.999), then Ho rejected and Ha accepted. Then it can be drawn the conclusion that there is an increase in student learning results by using cooperative learning model type Pair Checks on subject requirements, health and safety equipment in the class X Technic of Stoneand Concrete SMK Negeri 1 Palangka Raya 2015/2016.